Constitutionalism without rules: the guide dog case - Pomareda Muñoz, Diego Alonso (2020)
This investigation analyzes the deficiencies in the regulation of article 32 of the Sanitary Regulations for the Operation of Self-Services on which the Peruvian judicial system based to resolve the emblematic case related to Plaza Vea. In addition, we make a regulatory proposal in order to avoid that fundamental rights restrictions as a consequence of poor legislative technique. The problem investigated is that the Constitutional Court, in order to resolve the Plaza Vea case, did not take into consideration the regulatory prescriptive norms on which the prohibition related to the fact that animals cannot enter supermarkets is based. Therefore, we seek to demonstrate that, applying doctrinal concepts of legal argumentation such as vagueness, over-inclusion, irrelevant factual predicates, legal gaps and defeasibility, the Constitutional Court was able to understand that, rather than facing a collision of fundamental rights, we are faced with a deficient normative interpretation on which the controversy should have been resolved.